Qur’anic Ecofeminism as a Response to the Global Ecological Crisis: An Examination of Feminine Values in the Ecological Interpretation of the Qur’an - Zuhrupatul Jannah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Qur’anic ecofeminism offers an ethical and spiritual response to the global ecological crisis by integrating ecofeminist insight with Qur’anic theology. This study explores how feminine-coded values such as raḥmah (compassion), riʿāyah (nurturing care), and taʿāwun (cooperation) function as foundational principles of Qur’anic ecological ethics. Using a thematic (mawḍūʿī) approach, the article analyzes key Qur’anic verses alongside contemporary ecofeminist scholarship to show how domination-based paradigms toward both women and nature are challenged within the Qur’an. The findings demonstrate that the Qur’an frames the human–nature relationship within a moral horizon of compassion, relationality, and responsibility, thereby providing a theological basis for environmental protection that transcends gender binaries. Qur’anic ecofeminism thus contributes to the development of a just, sustainable, and spiritually grounded ecological ethic rooted in divine mercy and human stewardship.